A new species of Cyrtodactylus Gray (Gekkonidae: Squamata) from Manus Island, and extended description and range extension for Cyrtodactylus sermowaiensis (De Rooij) - Oliver, Paul M.; Hartman, Ryan; Turner, Cameron D.; Wilde, Taylor A.; Austin, Christopher C.; Richards, Stephen J. (Zootaxa, 2020)
Systematic investigations of vertebrate faunas from the islands of Melanesia are revealing high levels of endemism, dynamic biogeographic histories, and in some cases surprisingly long evolutionary histories of insularity. The bent-toed geckos in the Cyrtodactylus sermowaiensis Group mainly occur in northern New Guinea and nearby islands, however a further isolated population occurs on Manus Island in the Admiralty Archipelago approximately 300 km to the north of New Guinea. Here we first present a review of the genetic diversity, morphological variation and distribution of Cyrtodactylus sermowaiensis from northern New Guinea. Genetic structure and distributional records within Cyrtodactylus sermowaiensis broadly overlap with underlying Terranes in northern New Guinea, suggesting divergence on former islands that have been obscured by the infill and uplift of sedimentary basins since the late Pleistocene. Based on a combination of genetic and morphological differentiation we then describe the population from Manus Island as a new species, Cyrtodactylus crustulus sp. nov. This new species emphasises the high biological endemism and conservation significance of the Admiralty Islands, and especially Manus Island.